(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In the year 2001 A. Pena Graña found a small disk, 4 cm, in Covas (Ferrol, Coruña): it contains an inscription to the god REVE; it reads: AUG(UST)E REVE TRASANCI, but in a different syntactic order. Other specialists, F. Villar and B. Prósper, proposed another reading: REBE TRASANCIA+NCE (or TRASANCIANGE), being REBE a goddess, in opposition to REVE, a god. In a former article, I agreed with the first reading; in both papers we supposed that the name used for rivers in the area, REBE, was feminine. E. Arias, director of the museum of the Mariñas (Betanzos, Coruña), took a new picture of the disk, making possible a new, clearer, reading: VGE: UGE REBE TRASANCI; there is a break in the text, which made possible different readings. UGE can be a phonetic variant of the epithet of BANDI OGE: both are variants of the dative case, root *wegw -, ‘humid, to wet’; the theme would be *0gw i-, grade zero root, dative *0gei > Uge, or Oge, given the phonetic change > o. This etymological analysis of UGE / OGE is based on a frequent and very precise toponymy. In conclusion, OGE is not an isolated, obscure, divine name; OGE / UGE exists in the Galaico-Lusitanian pantheon. UGE REBE and REVE are the name of a god, a fluvial god.